Constructions of Leadership Identities via Narratives of African Women School Leaders - Moorosi, Pontso (Frontiers in Education, 2020)
The paper explores African women school leaders' constructions of their leadership identity. Using self-perception theory which sees changes in self-perceived leadership skills and dispositions as being related to changes in perceived leader identity, constructions of African women's leadership identity are mapped over a life-long career. Leader identity is, in this sense, inextricably linked to gender and an attempt is therefore made to understand these leader identities as gendered. The paper presents an analysis of the interviews of three women selected from a bigger study of 89 school leaders from four countries in sub-Saharan Africa. The three narratives of women leader identity construction are drawn from three of the four case study countries. The narrative approach to data analysis reflecting women school leaders' experiences of leader identity construction involved reading transcripts and coding them with themes characterizing the processes of becoming a leader and being identified as one. Findings suggest that processes of becoming a leader are influenced by women leaders' experiences of early socialization that gave them ways of doing leadership as well as values and attributes that shape their approach to leadership. These women grew up with a strong perception of who they are, and this instilled a sense of agency that facilitates leaderful actions. These actions were then affirmed through their different stages of growth and career development, thus strengthening their leader identity. It is concluded that understanding women leaders' experiences of leader identity is an important ingredient of leadership development.